Target temperature management in acute ischemic stroke - Gao, Lan; Yang, Ting; Chong, Hong; Wu, Longfei; Han, Jinming (Frontiers in Molecular Biosciences, 2026)
Acute ischemic stroke (AIS) is an acute neurological deficit that results from focal cerebral ischemia associated with permanent brain infarction, and is a leading cause of death and disability worldwide. Considerable attention has been paid to reducing mortality and improving the prognosis of patients with AIS. Targeted temperature management (TTM), including hypothermia therapy, normothermia control, and febrile intervention, has been widely investigated in laboratory and preclinical studies and has provided substantial protection for neurological function. The effect of TTM on neurological function prognosis in patients with AIS has attracted significant attention. This review summarizes the related mechanisms of action, clinical applications, and short- and long-term effects of TTM on neurological function in AIS, providing a clinical reference for the application and prognosis of TTM in patients with AIS.